2018
DOI: 10.17583/redimat.2018.2707
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception of Social Justice in Mathematics Classrooms

Abstract: The purpose of this study was to explore mathematics teachers’ perception of social justice in mathematics classrooms. We applied interpretive qualitative method for data collection, analysis, and interpretation through iterative process. We administered in-depth semi-structured interviews to capture the perceptions of three mathematics teachers about social justice in mathematics classroom at three public secondary schools in Kathmandu. We carried out multiple layers of thematic analysis and interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…They care about finding ways to teach mathematics to Roma children who struggle with them (as well as other children who also have troubles with this subject). This finding is consistent with previous literature highlighting the important role that teachers can play to transform learning and overcome structural inequalities [69]. As in the cases reported here, there are many teachers who really want to help Roma children, and they work hard to do so; but, sometimes good will is not enough.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They care about finding ways to teach mathematics to Roma children who struggle with them (as well as other children who also have troubles with this subject). This finding is consistent with previous literature highlighting the important role that teachers can play to transform learning and overcome structural inequalities [69]. As in the cases reported here, there are many teachers who really want to help Roma children, and they work hard to do so; but, sometimes good will is not enough.…”
Section: Discussionsupporting
confidence: 93%
“…Later studies confirmed Mead's findings [67,68]. This finding has been also confirmed in the field of mathematics education [69].…”
Section: Discussionsupporting
confidence: 63%
“…We employed qualitative interpretive inquiry as a research approach for this study. Interpretive inquiry relies on the normative or evaluative facts of data input, process, and outcome that best justifies the entire set of practices in which that concept is used (Plunket, 2013 as cited in Panthi et al, 2018). An interpretive inquiry develops knowledge assertions from the interpretation of lived experiences of the participants focusing on strategies of social justice in the mathematics classroom.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it should safeguard the right to education in mother tongue, guarantee the child rights and provide free basic education. (CDC, 2007, p. 19 as cited in Panthi et al, 2018) Hence, the document shows the policy of the government to provide equal access to education for all despite gender, age, and status of one's life (Panthi & Belbase, 2017). However, there is no seriousness in the concerned authorities to improve the quality of public education in Nepal leading to further deterioration of school mathematics curricular practice in the classrooms.…”
Section: Social Justice In Educational Policiesmentioning
confidence: 99%
See 1 more Smart Citation